2016
DOI: 10.1038/ncomms10698
|View full text |Cite
|
Sign up to set email alerts
|

Fear of large carnivores causes a trophic cascade

Abstract: The fear large carnivores inspire, independent of their direct killing of prey, may itself cause cascading effects down food webs potentially critical for conserving ecosystem function, particularly by affecting large herbivores and mesocarnivores. However, the evidence of this has been repeatedly challenged because it remains experimentally untested. Here we show that experimentally manipulating fear itself in free-living mesocarnivore (raccoon) populations using month-long playbacks of large carnivore vocali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
289
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(297 citation statements)
references
References 42 publications
(85 reference statements)
6
289
1
1
Order By: Relevance
“…Recent work by Zanette and colleagues [60, 61] used playbacks of predator vocalizations to effectively manipulate fear in songbirds ( Melospiza melodia ) and wild raccoons ( Procyon lotor ), demonstrating that innate fear alone has significant effects not only on the natural foraging decisions of diverse animals, but that these effects consequently affect the structure of the ecosystem. Thus, utilizing ethological approaches in both laboratory and field settings to understand the neural circuitry underlying innate fear signals and their roles in risky foraging decisions will undoubtedly prove fruitful.…”
Section: Ethological Approaches To Studying Fearmentioning
confidence: 99%
“…Recent work by Zanette and colleagues [60, 61] used playbacks of predator vocalizations to effectively manipulate fear in songbirds ( Melospiza melodia ) and wild raccoons ( Procyon lotor ), demonstrating that innate fear alone has significant effects not only on the natural foraging decisions of diverse animals, but that these effects consequently affect the structure of the ecosystem. Thus, utilizing ethological approaches in both laboratory and field settings to understand the neural circuitry underlying innate fear signals and their roles in risky foraging decisions will undoubtedly prove fruitful.…”
Section: Ethological Approaches To Studying Fearmentioning
confidence: 99%
“…Non-consumptive effects of predators, including the effects of fear, can play an important role in animal ecology, influencing offspring development (Lardner 2000;Dahl and Peckarsky 2002;Benard 2004), adult fitness (Roitberg et al 1979;Ylönen 1989;Dixon and Agarwala 1999;Gallagher et al 2016), population dynamics (Lima 1998;Preisser et al 2005;Creel et al 2009), and even ecosystem function Schmitz et al 1997;Suraci et al 2016). When risk of predation is high, animals spend more time being vigilant and less time foraging (Creel and Christianson 2008;Sheriff et al 2009;Wirsing and Ripple 2011), leading to poorer body condition and physiological stress.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research showed that experimental manipulations of fear in free-living mammalian mesopredators using month-long playbacks of intraguild top predator vocalizations caused cascading effects, reducing mesopredator foraging to the benefit of the mesopredator's prey, which in turn positively influenced multiple trophic levels in an intertidal food web (Suraci et al 2016). Similar experimental manipulations using visual (e.g.…”
Section: Future Research Directions Combining Experimental and Long-tmentioning
confidence: 99%
“…Recent empirical and experimental advances have highlighted the potential for top predators to help restore ecosystems and confer resilience against environmental challenges, e.g. biological invasions (Ritchie et al 2012, Suraci et al 2016. For example, the recolonization of the White-tailed Eagle Haliaeetus albicilla in the Finnish archipelago reduced American mink Neovison vison movements, potentially mitigating their impact on native species (Salo et al 2008).…”
Section: Superpredationmentioning
confidence: 99%